Green grams Kenya: Climate change risks and opportunities - Demissie, Teferi Dejene; Bolt, Jaclyn; Duku, Confidence; Groot, Annemarie; Recha, John W.M. (2019)
Agriculture in Kenya contributes to the national economy, food security, and employment of rural households. Climate change and weather variability affect agricultural production negatively and it is expected to worsen in the future. Climate-smart agriculture (CSA) practices present an opportunity to reduce such losses, build resilience in the agriculture sector, improve productivity and farmer incomes, and contribute to climate change mitigation (CIAT & World Bank, 2017). Green gram, also known as mungbean, maash or moong (Vigna radiata L.), is a potential food and cash crop in Kenya and grows well in arid regions, playing a key role in local food security. In the regions where stakeholders of the green grams value chain have been interviewed (Makueni, Kitui, Tharaka, Nithi), the area under production typically varies from 1-10 acres per household.